Evaluation of sound comfort in examination hall using acoustical environmental analyses - M., Mohd Amran; Masrol, Shaiful Rizal; Ismon, Maznan; Roslan, Mohd Nazrul; Yahya, Musli Nizam; Ghazali, Mohd Imran; Munawar, Shahruddin (Trans Tech Publications, 2013)
Acoustics environmental analyses were conducted in the unoccupied examination hall at Universiti Tun Hussein Onn Malaysia (UTHM), in order to determine the acoustical environment which reflects to sound comfort during sitting exam. The acoustic parameters that measured are background noise level, sound pressure level and reverberation time. The analysis result of untreated wall condition (without absorbent material) was revealed poor while treated wall condition (with absorbent material) revealed the improvement result. Installation of absorbent material on the wall and speakers rearrangement had reduced the highest background noise level of examination hall average reverberation times. A minor alteration at examination hall had contributed to better acoustic performance.